The Midnight Library - Kohara, Kazuno (New York, NY Square Fish, 2022)
"Once there was a library that only opened at night. Step inside and meet the little librarian and her three assistant owls"--
111238
Keywords: Libraries -- Pictorial works -- Juvenile fiction; Books and reading -- Pictorial works -- Juvenile fiction; Animals -- Pictorial works -- Juvenile fiction; Animals; Books and reading; Libraries; Picture books; Picture books